Characterizing / Segregating Municipal Solid Waste and Finding its Recycling Potential in Bannu District - Sareer Ahmad; Main Said Kashif; Jehangeer Alam; Abdul Ghani; Muhammad Irfan (Sir Syed University Research Journal of Engineering and Technology)
Investigating with rapid population growth and urban sprawl, unregulated municipal waste (MSW) poses a threat to public health and environmental safety. In this study, we examine its performance, cure, and physiological features and evaluate the potential of MSW as a renewable energy source in the Bannu region. Depending on the average generation of MSW generation (e.g. 0.439 kg/capita/day), the daily production of MSW in the city can reach up to 2000 tons/day. However, its safe construction is prohibited directly to a lack of (a) past planning, (b) public services, (c) political determination, and (d) public understanding. Various MSW samples were collected for social and economic construction. Body parts of MSW in Bannu are declining through decaying material, plastic bags of nylon, cloth, nappy and paper. A close assessment of this MSW was performed along with its temperature values. The maximum temperature range for MSW is estimated at 13369.935 kJ / kg. The power output of 44.29 MW is continuously tested from 2000 tons of MSW / day. The consequences of this study should help policymakers develop a management strategy for MSW for renewable power.